The Impact of COVID-19 Pandemic on University Faculty, Staff, and Students and Coping Strategies Used During the Lockdown in the United Arab Emirates - Al Miskry, Abdullah Seif Abdullah; Hamid, Abdalla A. M.; Darweesh, Abdel Hameed M. (Frontiers in Psychology, 2021)
Introduction: The COVID-19 pandemic and the subsequent lockdown instigated serious mental health conditions. So far, the UAE data on mental health problems due to this pandemic outbreak is still scarce. The objective of this study was to identify the prevalent psychological difficulties experienced by university students, faculty members, and staff during COVID-19 lockdown and the coping strategies used. Methods: A cross-sectional design was used to collect data from 737 participants using an online electronic survey. Participants included students, faculty members, and staff from universities in the UAE. The General Health Questionnaire (GHQ-12) was used to measure general distress, Penn State Worry Questionnaire (PSWQ-16) was used to measure worry, and the Coping Inventory for Stressful Situations (CISS-48) was administered to measure coping strategies used by participants during the COVID-19 pandemic lockdown. Data were collected during May to June 2020. Results: The results indicated that 60.4% of students, 57.4% of the faculty members, and 52.3% of the staff experienced mild psychiatric problems. About 32.9% of students, 33.7% of the faculty members, and 25% of the staff experienced high levels of worry during the COVID-19 lockdown. Changes in eating patterns, worsening chronic health problems, change in sleep patterns, and concentration difficulties were reported. Furthermore, significant differences were observed in worry and coping strategies among participants. Women use more avoidance and emotion-focused coping compared to men. Conclusion: It was concluded that COVID-19 lockdown has negatively impacted university faculty, staff, and students in terms of health behavior, psychological and physical health.